Recommendations for the use of sensor‐augmented pumps with predictive low‐glucose suspend features in children: The importance of education. Issue 8 (19th January 2017) - Scaramuzza, Andrea E; Arnaldi, Claudia; Cherubini, Valentino; Piccinno, Elvira; Rabbone, Ivana; Toni, Sonia; Tumini, Stefano; Candela, Gilberto; Cipriano, Paola; Ferrito, Lucia; Lenzi, Lorenzo; Tinti, Davide; et al.
Abstract : Abstract: Sensor‐augmented pumps, which consist of a pump and a continuous glucose monitoring system, offer considerable therapeutic opportunities, despite requiring close attention in the early phase of their use. The aim of this paper is to provide recommendations on the use of a predictive low glucose management (PLGM) system (Minimed 640G™, Medtronic, Northridge, CA, USA) in adolescents with type 1 diabetes either at the start of therapy or during follow‐up. Sound clinical recommendations on PLGM are of increasing importance since several recent papers have reported significant clinical improvements in patients with PLGM, especially in adults. These recommendations are based on the experience of a group of pediatric endocrinologists who collaborated to closely and intensively study the on‐boarding of adolescent patients with type 1 diabetes on automated systems to gain first‐hand experience and peer‐to‐peer insights in a unique free‐living environment. The suggestions provided here are indicative, so can be adapted to the individual realities and experiences of different diabetes centers. However, we believe that close adherence to the proposed scheme is likely to increase the chances of improving the clinical and metabolic outcomes of patients treated with this therapy.